Em nome do pai: religião, política e os caminhos da democracia no Brasil - Igor Rafael Torres Santos (2021)
The three essays that compose this research represents the resurgence of the theological-political in contemporary Brazilian context, whose specificity is in the crescent evangelical pattern. Differently from the analyzes that depart from religion itself to comprehend it socially, we pursue to think the religious and theological-political element from the dimensions of everyday life, of politics and democracy and, fundamentally, from the dimension of the late capitalism secular space-time. This means to say that the analyzes do not focus on the phenomenal forms of evangelical participation in politics; they try to comprehend this resurgence roots and its possible consequences for the fragile Brazilian democracy and for sociability in general. They also pursue to think the religious and theological-political element based on the contradictions of Brazilian neoliberal capitalism, whose specific process of domination and reproduction explodes as an urban tragedy in our society. In this sense, evangelical Christianity appears in our research as one of the ideological forms that regulate everyday life under capitalism, and the theological-political as a social form that aims to subordinate politics to religion by denying the constitutive characteristics of politics and democracy, while seeking to maintain the capital order as if it were a divine order. As evangelicals do not constitute a homogeneous social group, institutionally and doctrinally, it was necessary to build a concept that embraced continuities in these differences, which would support our analysis about the evangelical pattern of this political theology and its impact in the Brazilian society. We believe that the concept of Religious Device satisfactorily answered this need, since, with it, we can think about power relations and ideologies that circulate in a similar way in different Brazilian evangelical communities. Because, if the theological-political reappears and advances in our society, it is because certain theologies are shared by different groups and certain political projects of power are reproduced and internalized by them. Among these theologies, we believe that the Theology of Prosperity and Positive Confession, added to the Theology of the Neo-Calvinist Worldview, actually are the most influential theologies in the country and, therefore, those that most correspond to the needs (economic, political, cultural) of neoliberal sociability. In turn, a reactionary populist experience, also influenced by a certain evangelical strand, has emerged in the Brazilian political scenario as a political power project, whose fundamental political characteristics are based on a friend-enemy relationship and on a non-acceptance of difference as a constitutive element of urban collectivity still developing in our society.